Yishen paidu pills attenuates 5/6 nephrectomy induced kidney disease via inhibiting the PI3K/AKT/mTOR signaling pathway - Liu, Saiji; Cao, Yiling; Yuan, Qian; Xie, Yaru; Zhu, Yuting; Yao, Lijun; Zhang, Chun (Frontiers in Pharmacology, 2024)
Introduction: Chronic kidney disease (CKD) is a substantial global health issue with high morbidity and mortality. Yishen Paidu Pills (YSPDP) are effective concentrated water pills composed of four herbs developed by Wuhan Union Hospital to treat CKD. However, the mechanism of YSPDP action is largely unknown. This study combined metabolomics, network pharmacology, transcriptomics, and experimental verification to elucidate and identify the effects and potential mechanisms of YSPDP against CKD.Methods: Firstly, we used metabolomics analyses to identify the chemical components of YSPDP.Then, network pharmacology was conducted and indicated the predicted signaling pathways regulated by YSPDP. Next, we conducted a 5/6 subtotal nephrectomy (5/6 SNx) rat model and treated these rats with YSPDP or Losartan for ten weeks to evaluate the effect of YSPDP on CKD.To further analyze the underlying mechanism of YSPDP in CKD, the kidney tissues of 5/6 SNx rats treated with vehicle and YSPDP were performed with transcriptome sequencing. Finally, the western blot was performed to validate the signaling pathways of YSPDP against CKD.Results: Twenty-four classes of chemicals were identified by metabolomics in YSPDP. YSPDP markedly hindered CKD progression, characterized by the restoration of body weight and serum albumin levels, improved renal function, diminished tissue injury, and hampered renal fibrosis in 5/6 SNx rats. The efficacy of YSPDP in ameliorating the progression of CKD was comparable to that of losartan. Furthermore, network pharmacology, transcriptomics, and functional enrichment analysis indicated the PI3K/AKT/mTOR signaling pathway was the key pathway regulated by YSPDP.Western blot validated the inhibition of PI3K/AKT/mTOR signaling in the kidney of 5/6 SNx rats treated by YSPDP.The study identified the chemicals of YSPDP and revealed that YSPDP prevented the progression of CKD by inhibiting PI3K/AKT/mTOR signaling in 5/6 SNx rats.